The elements of modern architecture understanding contemporary buildings - Radford, Antony; Morkoç, Selen B. (Selen Bahriye); Srivastava, Amit (Architect) (Thames & Hudson, 2014)
"Dissects fifty of the world's modern masterpieces, constructed from 1950 to the present, through specially commissioned freehand drawings that reveal the principles and details of what makes a building meaningful and enduring. Starting from its site, each work is analyzed through its surroundings, use of natural light, volume and massing; its program and circulation; and its details, fenestration and ornamentation, showing the reader how the building works as a cohesive whole." --Back Cover.